2003
DOI: 10.1021/ja035329+
|View full text |Cite
|
Sign up to set email alerts
|

Diradical Mechanisms for the Cycloaddition Reactions of 1,3-Butadiene, Benzene, Thiophene, Ethylene, and Acetylene on a Si(111)-7×7 Surface

Abstract: The cycloaddition chemistry of several representative unsaturated hydrocarbons (1,3-butadiene, benzene, ethylene, and acetylene) and a heterocyclic aromatic (thiophene) on a Si(111)-7x7 surface has been explored by means of density functional cluster model calculations. It is shown that (i) 1,3-butadiene, benzene, and thiophene can undergo both [4+2]-like and [2+2]-like cycloadditions onto a rest atom-adatom pair, with the former process being favored over the latter both thermodynamically and kinetically; (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
58
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 48 publications
13
58
0
Order By: Relevance
“…[281]. c 2007, The American Chemical Society such as acrylonitrile [315], 1,3-cyclohexadiene [300], and 1,3-butadiene [307] even more than these reactions are favored on Si(100)-2×1. Interestingly, the asymmetric and highly polar acrylonitrile [315] that forms a [4 + 2]-product of the type Si-CH 2 -CH=C=N-Si confirmed by a vibrational band ν C=C=N = 2028 cm −1 [378], can bind in two different ways with respect to the adatom-rest atom pair: with the nitrogen bound to adatom and with the nitrogen bound to the rest atom.…”
Section: Si(111)-7×7 Chemistry: Parallels Between Surface Dimers and mentioning
confidence: 99%
“…[281]. c 2007, The American Chemical Society such as acrylonitrile [315], 1,3-cyclohexadiene [300], and 1,3-butadiene [307] even more than these reactions are favored on Si(100)-2×1. Interestingly, the asymmetric and highly polar acrylonitrile [315] that forms a [4 + 2]-product of the type Si-CH 2 -CH=C=N-Si confirmed by a vibrational band ν C=C=N = 2028 cm −1 [378], can bind in two different ways with respect to the adatom-rest atom pair: with the nitrogen bound to adatom and with the nitrogen bound to the rest atom.…”
Section: Si(111)-7×7 Chemistry: Parallels Between Surface Dimers and mentioning
confidence: 99%
“…Finally, it is noted that a previous theoretical investigation of thiophene chemisorption on this surface, using a Si 16 H 18 cluster or unit cell fragment to model the surface [13], demonstrated that chemisorption is stepwise and that there are two activation energy barriers associated with the process. The first barrier was calculated to be 0.234 eV, above the energy of the isolated molecule/surface system, and the second barrier was calculated to be 0.061 eV above the energy of an intermediate state.…”
Section: Discussionmentioning
confidence: 87%
“…The first STM investigation of thiophene adsorbed onto the Si(111)-7×7 surface noted that at low coverage, thiophene does not distribute randomly over the available bonding sites but chemisorbs preferentially on edge adatoms in the faulted half of the unit cell [13]. This site preference has been observed for other simple aromatic molecules on the 7×7 surface, including benzene [3] and chlorobenzene [14].…”
Section: Introduction In 1997 Hamers Et Al Demonstratedmentioning
confidence: 95%
“…In another study, Lu et al [30] found a binding energy of -31.3 kcal/mol, considering a 6-layer tube, while first principles calculations were also performed [31]. Most recently, sidewall epoxidation of SWCNTs was studied with ONIOM [32].…”
Section: Ozonolysismentioning
confidence: 99%